Geopatrimônio de Prudentópolis (PR): valorização e divulgação por meio do geoturismo e educação não formal - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
rudentópolis is a municipality in the southeastern mesoregion of the state of Paraná, south of the brazilian territory, located on the Paraná Sedimentary Basin. The municipality has a peculiar geodiversity, with rocks originating at important moments in the history of the Earth, fossil records that stand out, and unique geoforms, such as canyons and large waterfalls. The history of planet Earth left interesting and varied chapters in what is today the territory of Prudentópolis, however, this content is still spread in a precarious way and certainly insufficient for the community in general. This work, whose object of research is geodiversity and geoheritage in the municipality of Prudentópolis, Paraná, seeks, through geotourism and non-formal educational processes, to assist in the public dissemination of knowledge about geodiversity and to contribute to the sustainable development of the territory. Thus, it was defined as the general objective of the research, to verify the elements of geodiversity, in the municipality of Prudentópolis, that fit to constitute the local geoheritage, as a way to support initiatives of geotourism and non-formal education in geosciences. To this end, a survey was carried out on the geodiversity of the municipality to define its geoheritage, defined by nineteen selected points, the geosites. The set of information allowed the creation of didactic materials - geotouristic map and didactic vídeo -, thinking about reaching society mainly in a non-formal way, and also contributing to the development of cultural and sustainable tourism, through geotourism. In the elaboration of these materials, we sought to represent spatially the main contents raised during the investigation, emphasizing their stratigraphic exceptionality and their unique forms of relief. With simplified and accessible information, these materials were sought to provide tangible support for the implementation of the dissemination and conservation strategy. The information gathered on the geodiversity and geoheritage of Prudentópolis exposes valuable content for education and culture in the municipality. Its territory is distributed over the paleozoic and mesozoic rocks of the Paraná Sedimentary Basin, originating at important moments in Earth's history, before the opening of the South Atlantic Ocean, when the Pangea supercontinent still dominated. Its rocks are linked to formation environments that range from marine to fluvial continental or desert ones (Serra Alta, Teresina, Rio do Rasto and Piramboia Formation), in addition to the sandstone rocks originated from the Botucatu mega desert and the volcanic and subvolcanic rocks of the Serra Geral Group. Its geographical location, in the morpho-sculptural transition from the Second to the Third Plateaus of Paraná State, gives it a unique landscape, with hundreds of waterfalls, residual reliefs, and unique geoforms, which allow a basic understanding of the origin and evolution of the regional relief. As this content becomes accessible to the community, managers and tourists, in the medium and long term it is possible that the population's relationship with geosites will become more affective and that a feeling of belonging and appropriation by geoheritage will develop, and that, thus, geoconservation measures can materialize.
Keywords: Bacia Sedimentar do Paraná; Geodiversidade; Patrimônio Geológico; Geoconservação; Desenvolvimento sustentável; Paraná Sedimentary Basin; Geodiversity; Geological Heritage; Geoconservation; Sustainable development; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA